Effect of Magnetic Field Energy on Growth of Aspergillus flavus and Aflatoxins production - Ahmad, Aiman M; Yahya, Abdul Ghani I; Jabir, Abdul Wahid Sh (Al-Nahrain Journal of Science, 2013)
The study was conducted to determine the impact of the magnetic field poles on aflatoxins produced by Aspergillus flavus. The subjected fungus to the northern pole, southern pole, both poles and their influences were compared with the control at which the fungus was not affected by magnetic field energy. Aspergillus flavus was influenced by magnetic field energy which applied through a magnet at different forces (5, 7,10,30,50 Gauss) for seven days at temperature of 27 oC. There are no different between the uses of magnate with 5 or 50 Gauss. The effect of magnetic field poles was observed on the growth of Aspergillus flavus on solid and liquid media. The southern pole had a positive effect on the growth of Aspergillus flavus by increasing the diameter of the colony or the turbidity of growth medium, while the northern pole had a negative influence on the growth of A. flavus, diameter or the turbidity, while the treatment of northern and southern poles together and the control treatment are equal. The most important conclusion that have been observed was the effect of magnetic field poles on the concentration of total aflatoxin produced by A. flavus, which was 454.73 ppb (when treated with southern pole) and 25.40 ppb (when treated with northern pole) while the control 212.46 ppb and both poles 88.33 ppb by using ELISA technique.